Przegląd budownictwa drewnianego na terenie Szwecji od okresu wędrówek ludów do wczesnego średniowiecza - Barnycz-Gupieniec, Romana (Acta Universitatis Lodziensis. Folia Archaeologica, 1982)
Swedish excavations with preserved remnants of wooden architecture, known from the literature of the subject, constitute quite big materials basis. It allows to follow along a wider time-span changes which were occuring in the form and construction of housing units. At the time of migration of nations (400-500 A.D.) in Sweden prevail the so-called hall-houses, built on a rectangle plan. Their length amounts to 20-40 mts, but there can be met longer houses reaching 60 mts. Their width ranges from 8 to 10 mts. Shorter houses, with the length of 10-15 mts and width of 6 to 8 mts, are less numerous. All houses had stone foundations. The walls had plaited construction covered with clay. This form of construction was exerting an influence on the roof construction. There were preserved numerous holes in poles running parallelly in two rows, sporadically in four, in side the house along its longer axis. The roof was supported on them. The floor consisted of a layer of beaten ground or clay. More or less in the middle of the house there was standing a fire place although not each unit possessed it. A very characteristic featre was occurrence of houses with slightly arched longer walls.